Transformations of Research into Professional Activities - Poviliūnas, Arūnas (Sociologija. Mintis ir veiksmas, 2001)
The article elaborates a programme based on Pierre Bourdieu’s sociology for research into the field of professional activities. This programme is considered from the viewpoint of the development of the sociology of professions. The article analyses the different stages of the development of the sociology of professions and reveals how the typological and functionalistic concept of the profession and research into the professionalisation of occupations become interpretations of professional power. The author argues that the conceptual tools offered by Bourdieu (field, habitus and capital) usefully contribute to the investigation of professions as forms of professional power.
Keywords: sociology of professions; occupations; professions; professionalization; theory of P. Bourdieu; field and habitus; the research of the field of professional activity